Peningkatan Ekonomi Masyarakat Melalui Edukasi Literasi Keuangan Islam - Vahlevi, Dewi Riza Lisvi (Proceedings of Annual Conference for Muslim Scholars, 2022)
Understanding of Islamic financial literacy should have been applied at least in personal finance, because when someone can manage finances well, it means that person has intelligence in managing personal finances. This article tries to explore how the process of educating the public about Islamic financial literacy in an effort to improve their economic level. Using the literature review method and field research, this article confirms that Islamic financial literacy plays an important role in improving the community's economy. In practice, Islamic financial literacy is really able to improve the community's economy starting from their personal finances.